Sunday

March 29, 2015

March 29, 2015

Posted by **Jake** on Monday, January 9, 2012 at 11:06pm.

I am not sure if this right.

1. solve rational equation

A) (x+3)/(x-1)=2x+1

x+3=(2x+1)(x-1)

x+3=2x^2 - 2x + x - 1

??

- Math -
**Reiny**, Tuesday, January 10, 2012 at 1:00amcollect all like terms to get a quadratic equation

2x^2 - 3x - 4 = 0

use the formula to solve for x

- Math -
**Jake**, Tuesday, January 10, 2012 at 1:11amSo I have to use quadratic formula right? If so, no wonder I don't get the answer

- correction - Math -
**Reiny**, Tuesday, January 10, 2012 at 1:22amI think I added the x terms up incorrectly

should have been

2x^2 - 2x -4 = 0

divide by 2

x^2 - x - 2 = 0

now it factors

x(-2)(x+1) = 0

x = 2 or x = -1

**Answer this Question**

**Related Questions**

ALGEBRA - How do you solve the rational equation: (n/n-2)+(n/n+2)=(n/n^2-4) I ...

Math-Rational #'s - Just trying to understand this. Please let me know if I did ...

math3333 - y+2/y =1/y-5 *Please solve the rational equation I am not certain if ...

Chemistry - I have the question find the balanced equation when Fe(s) is placed ...

Math - Using the intersection method, I need to solve the following equation: 5x...

math - Solve the equation. -6p - 21 = 3p - 12 A. 1 B. 3 C. –3 D. –1 im sure its...

intermidate algebra - solve equation(rational expression) 3/10=5/x 3x=50 x=50/3 ...

Math(dispute to previous question) - 2)Name the sets of numbers to which 457 ...

pre-calc Question on a previous question - On the question below, Bob Pursley ...

Math - If 6 is increased by 4 times a number, the result is 68. A.Write and ...